2012
DOI: 10.1182/blood-2011-12-395186
|View full text |Cite
|
Sign up to set email alerts
|

Chronic HIV infection affects the expression of the 2 transcription factors required for CD8 T-cell differentiation into cytolytic effectors

Abstract: CD8 T cells lose the capacity to controlHIV infection, but the extent of the impairment of CD8 T-cell functions and the mechanisms that underlie it remain controversial. Here we report an extensive ex vivo analysis of HIV-specific CD8 T cells, covering the expression of 16 different molecules involved in CD8 function or differentiation. This approach gave remarkably homogeneous readouts in different donors and showed that CD8 dysfunction in chronic HIV infection was much more severe than described previously: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
2
18
2
Order By: Relevance
“…Nevertheless, given that recent studies have shown that T-bet expression is co-localized both in the nucleus and cytoplasm [50], our results further suggest that HIV-specific CD8+ T cells in HIV chronic progressors might have high abundance of T-bet in the cytoplasm, leading to the inability to repress the expression of inhibitory receptors and induce cytolytic functions. However, a recent study by Ribeiro-dos-Santos et al concluded that loss of cytolytic potential of HIV-specific CD8+ T cells was a consequence of both T-bet and Eomes down-regulation in the chronic phase of HIV infection [51]. The discrepancies between this study and our results here are most likely due to the use of different techniques to observe the levels of transcription factors.…”
Section: Discussioncontrasting
confidence: 97%
“…Nevertheless, given that recent studies have shown that T-bet expression is co-localized both in the nucleus and cytoplasm [50], our results further suggest that HIV-specific CD8+ T cells in HIV chronic progressors might have high abundance of T-bet in the cytoplasm, leading to the inability to repress the expression of inhibitory receptors and induce cytolytic functions. However, a recent study by Ribeiro-dos-Santos et al concluded that loss of cytolytic potential of HIV-specific CD8+ T cells was a consequence of both T-bet and Eomes down-regulation in the chronic phase of HIV infection [51]. The discrepancies between this study and our results here are most likely due to the use of different techniques to observe the levels of transcription factors.…”
Section: Discussioncontrasting
confidence: 97%
“…The CD56+ CD8 T cells expressing T-bet mostly co-expressed EOMES (Figure 3A). In contrast, a large proportion of CD56- cells were negative for both T-bet and EOMES (Figure 3A), a phenotype predicted to have reduced lytic effector function [23], [24]. Recently, HIV infection was shown to downregulate both of these transcription factors in CD8 T cells [23].…”
Section: Resultsmentioning
confidence: 98%
“…Recent studies found that another transcription factor, Eomes, regulates IFN-γ production by T-cells in intracellular infections (28), but it has both positive and negative regulatory effects depending on the infection (29, 30). The role of Eomes in Mtb infection is not known.…”
Section: Resultsmentioning
confidence: 99%